2016
DOI: 10.1016/j.ejogrb.2016.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Medical students learning experiences of the labour ward: a qualitative research study

Abstract: Bedside teaching was highly valued as it advanced student's knowledge of obstetrics theory and improved communication skills. In general, medical students reported a positive experience from working in the labour word but there is scope for improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Finally, as active participation in acute situations and immediate debriefing were considered an important learning experience, we suggest structurally embedding multidisciplinary debriefings at placements in these contexts. Our students expressed concern about the diverse size of clinical placements and differences in learning opportunities, which is in line with international findings 7,11 . Over the last years, there has been an increase in the number of medical and midwifery students at placements, which has created a competitive atmosphere in terms of learning opportunities.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Finally, as active participation in acute situations and immediate debriefing were considered an important learning experience, we suggest structurally embedding multidisciplinary debriefings at placements in these contexts. Our students expressed concern about the diverse size of clinical placements and differences in learning opportunities, which is in line with international findings 7,11 . Over the last years, there has been an increase in the number of medical and midwifery students at placements, which has created a competitive atmosphere in terms of learning opportunities.…”
Section: Discussionsupporting
confidence: 83%
“…Semi-structured interviews were held in Dutch. An interview guide with open-ended questions, derived from a review of the literature 6,9,11 , was used ( Table 1).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Midwives and medical students demonstrated significant differences between their expectations of medical student involvement in facilitating a delivery, performing a well-baby check and providing advice on breastfeeding (Quinlivan, 2003). A recent study reported that students felt as though they missed out on valuable learning opportunities because they were unclear of their role (Cotter, 2016).…”
Section: Everyone Needs To Know Their Rolementioning
confidence: 99%
“…Specific adjustments to the medical education curriculum have been identified to enhance student learning and improve student perception of O&G. One such adjustment includes the addition of pre-learning material made available to students prior to their rotation in O&G. Improving student confidence through provision of pre-learning material to ease the transition from pre-clinical theory to clinical learning may be necessary to improve student experience and enhance acquisition of knowledge and skills on the labour ward (Johnson 2012;Amorosa 2012). Students often feel frustrated with unclear learning objectives and have identified pre-learning material with prespecified learning aims as important (Cotter, 2016). Students have noted the need for a 'refresher' course on the focused skill-set required for the O&G rotation, as well as clearer links between theory and clinical practice (Johnson, 2012).…”
Section: Introductionmentioning
confidence: 99%